1986
DOI: 10.1001/jama.1986.03370240067039
|View full text |Cite
|
Sign up to set email alerts
|

Review of Urine Microscopy for Bacteriuria

Abstract: Urine microscopy for bacteriuria remains a useful and valid technique for the evaluation of urinary tract infection; however, established interpretive criteria are not agreed on. Our own data and a review of the literature demonstrate that reliable data can be obtained by enumerating the organisms observed in stained or unstained centrifuged and stained uncentrifuged urine specimens. Criteria are given for the interpretation of urine microscopy for maximum sensitivity and specificity for each method reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Lastly, Jenkins et al reviewed approximately 40 publications relating to urine microscopy for bacteriuria and found a variety of approaches which included examination of stained and unstained, centrifuged and uncentrifuged specimens (31). As a result of their review, they suggested criteria for interpretation of urine microscopy for maximum sensitivity and specificity.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Lastly, Jenkins et al reviewed approximately 40 publications relating to urine microscopy for bacteriuria and found a variety of approaches which included examination of stained and unstained, centrifuged and uncentrifuged specimens (31). As a result of their review, they suggested criteria for interpretation of urine microscopy for maximum sensitivity and specificity.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Some have been directed at the detection of pyuria, including microscopic examination for the presence of white blood cells 1 ' 2,3 and the leukocyte esterase test. 4 ' 5 Others have been directed at the detection of bacteriuria, including microscopic examination for the presence of microorganisms, 3,[6][7][8][9][10] the bacterial nitrite test, 4 -5 bioluminescent detection of bacterial adenosine triphosphate, [11][12][13][14] filtration with colorimetric detection of microorganisms, 13 ' [15][16][17] and rapid detection of growth of organisms using various physical or chemical culture characteristics. 11,13 ' 18-20 Microscopic techniques for the detection of microorganisms have included the examination of stained or unstained urine that has been uncentrifuged, centrifuged by conventional techniques, or centrifuged by the slide cytocentrifuge technique.…”
mentioning
confidence: 99%
“…11,13 ' 18-20 Microscopic techniques for the detection of microorganisms have included the examination of stained or unstained urine that has been uncentrifuged, centrifuged by conventional techniques, or centrifuged by the slide cytocentrifuge technique. 3 ' [6][7][8][9][10] The Gram stain performed on urine centrifuged by the slide cytocentrifuge technique seems to have several advantages over other available screening tests. It is easier to interpret than other microscopic techniques, 7 and, unlike nonmicroscopic techniques, has the potential to give morphologic information in positive cases.…”
mentioning
confidence: 99%
“…3 The ecacy of microscopy as a screening test for bacteriuria varies widely: sensitivities range from 60% to 100% and speci®cities from 49% to 100% 4 . A major factor is the lack of standardisation both in technique and in the criteria for de®ning abnormal results; however, if these are carefully standardised, a sensitivity and speci®city up to 95% can be attained.…”
Section: Discussionmentioning
confidence: 99%
“…A major factor is the lack of standardisation both in technique and in the criteria for de®ning abnormal results; however, if these are carefully standardised, a sensitivity and speci®city up to 95% can be attained. 4 Falsely negative urine leukocytes counts are caused by loss of leukocytes during the centrifugation of the urine, and a delayed examination of urine can result in a reduction in sensitivity due to lysis of leukocytes. 5 Microscopy as a screening test for bacteriuria and leukocyturia requires special equipment and training of personnel.…”
Section: Discussionmentioning
confidence: 99%